Evidence base for an intervention to maximise uptake of glaucoma testing: a theory-based cross-sectional survey. Issue 2 (1st March 2012) - Prior, Maria; Burr, Jennifer M; Ramsay, Craig R; Jenkinson, David; Campbell, Susan; Francis, Jillian J; ,
Abstract : Objective: To identify factors associated with intention to attend a hypothetical eye health test and provide an evidence base for developing an intervention to maximise attendance, for use in studies evaluating glaucoma screening programmes. Design: Theory-based cross-sectional survey, based on an extended Theory of Planned Behaviour (TPB) and the Common Sense Self-Regulation Model, conducted in June 2010. Participants: General population including oversampling from low socioeconomic areas. Setting: Aberdeenshire and the London Boroughs of Lewisham and Southwark, UK. Results: From 867 questionnaires posted, 327 completed questionnaires were returned (38%). In hierarchical regression analysis, the three theoretical predictors in the TPB (Attitude, Subjective norm and Perceived Behavioural Control) accounted for two-thirds of the variance in intention scores (adjusted R 2 =0.65). All three predictors contributed significantly to prediction. Adding 'Anticipated regret' as a factor in the TPB model resulted in a significant increase in prediction (adjusted R 2 =0.74). In the Common Sense Self-Regulation Model, only illness representations about the personal consequences of glaucoma ( How much do you think glaucoma would affect your life? ) and illness concern ( How concerned are you about getting glaucoma? ) significantly predicted. The final model explained 75% of the variance in intention scores, with ethnicity significantly contributing to prediction. Conclusions: In this population-based sample (including over-representation of lower socioeconomic groupings), the main predictors of intention to attend a hypothetical eye health test were Attitude, Perceived control over attendance, Anticipated regret if did not attend and black ethnicity. This evidence informs the design of a behavioural intervention with intervention components targeting low intentions and predicted to influence health-related behaviours.